Personalized principal leadership practices : eight strategies for leading equitable, high achieving schools - McLaughlin, Dionne V. (Emerald Publishing Limited, 2020)
Personalized Principal Leadership Practices includes practical solutions to problems principals encounter as they endeavor to solve vexing problems with the underachievement of students of color. Featuring principals which lead schools where 80% or more of African American and Latinx students are proficient on State's standardized English and Math assessments, McLaughlin examines the strategies expert principals utilize: personalizing data by amplifying student academic stories, conducting ORID data chats, developing principal-directed student equity learning goals and increasing teachers' cultural proficiency. Readers are introduced to equity audits, equity focused classroom walkthroughs, student-led equity discussion panels and affinity groups, school-wide intervention programs, including a system for Not Handed ins (NHIs) for missed assignments, and strategies for building trusting relationships with families of color.
Includes index.
Keywords: Teacher-principal relationships.; Leadership.; Minorities -- Education.; Education -- Administration / School Superintendents & Principals.; Teaching staff.; elektronické knihy; electronic books